2017
DOI: 10.1017/ice.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infections in Neonates Following Mupirocin-Based MRSA Decolonization: A Multicenter Cohort Study

Abstract: Objective To characterize the risk of infection after Staphylococcus aureus decolonization with intranasal mupirocin. Design Multicenter, retrospective cohort study. Setting Tertiary care neonatal intensive care units (NICUs) from three urban hospitals in US. Bed size range: 45–100. Methods MRSA-colonized neonates were identified from NICU admissions occurring from January 2007–December 2014, during which a targeted decolonization strategy was used for MRSA control. In two time-to-event analyses, MRSA-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Moreover, the importance of new screening methods, such as polymerase chain reaction and whole-genome sequencing, needs to be defined [6, 7, 10, 16, 64]. Since MRSA resistant to mupirocin and antiseptics have been reported [18, 44, 71], the efficacy of nasal mupirocin application in primary and persistent MRSA decolonization warrants verification [10, 70, 72], Finally, potential adverse effects of antiseptic baths, such as skin irritation and toxicity [73], as well as nonantimicrobial strategies like maternal skin-to-skin contact for MRSA decolonization remain subjects of discussion [74]. …”
Section: Treatment and Prevention Of Neonatal Mrsa Infectionsmentioning
confidence: 99%
“…Moreover, the importance of new screening methods, such as polymerase chain reaction and whole-genome sequencing, needs to be defined [6, 7, 10, 16, 64]. Since MRSA resistant to mupirocin and antiseptics have been reported [18, 44, 71], the efficacy of nasal mupirocin application in primary and persistent MRSA decolonization warrants verification [10, 70, 72], Finally, potential adverse effects of antiseptic baths, such as skin irritation and toxicity [73], as well as nonantimicrobial strategies like maternal skin-to-skin contact for MRSA decolonization remain subjects of discussion [74]. …”
Section: Treatment and Prevention Of Neonatal Mrsa Infectionsmentioning
confidence: 99%
“…The absence of NEC and non-SA clinical infections in our study and elsewhere is also reassuring. 31 Finally, emergence of mupirocin-resistant strains was uncommon in our population, as it has been in other NICU decolonization programs. 8,33 Resistant strains appeared in enrollment swabs at 1 site, but we cannot determine whether the cause was our intervention or the introduction of a resistant strain from an exogenous source.…”
Section: Figurementioning
confidence: 71%
“…29 Various targeted MRSA decolonization programs for infants in the NICU have been evaluated retrospectively by using historical controls as the comparator. 28,30,31 In some instances, infants who had been recolonized were retreated. Each of these studies revealed a treatment effect; however, the duration of the effect, the impact of retreatment, and the effect of secular changes cannot be fully elucidated when historical controls are used.…”
Section: Figurementioning
confidence: 99%
“…Data showing efficacy and safety of S. aureus decolonization to reduce infection risk are primarily available from observational studies and a recent randomized trial that was not powered to detect a reduction in S. aureus infections. 6,29,30,[35][36][37] Even though decolonization has included treatment with topical antibiotics, topical antiseptics, and rarely, systemic antimicrobials, intranasal mupirocin alone is most commonly used. Intranasal mupirocin is not approved by the US Food and Drug Administration (FDA) for this indication in neonates, yet numerous studies reporting the use of mupirocin for S. aureus decolonization have not identified any clinically relevant adverse effects.…”
Section: Questionmentioning
confidence: 99%
“…Small retrospective studies have suggested that undetected MRSA carriers that are not placed on contact precautions pose a significant risk to other patients within the unit. 36 However, if healthcare personnel perceive admitted neonates to be at low risk of MRSA colonization, then preemptive contact precautions are likely not indicated. Some states mandate screening all neonates, even those at low risk of colonization.…”
Section: Questionmentioning
confidence: 99%